Local, environmental and trace metal effects on gut microbiota diversity in urban feral pigeons - Schmitt, Clarence; Gasparini, Julien; Moullec, Héloïse; Walch, Laurence; Leroux-Coyau, Mathieu; Leloup, Julie (ACADEMIC PRESS INC ELSEVIER SCIENCE, 2025)
Nowadays, understanding the biotic responses to the enhanced urbanization need to encompass not the only the physiological and phenotypic features but also the related microbiota of wildlife animals. One of main threats in urban ecosystems is the chemical pollution. Thus, we have explored whether the cloacal microbiota of feral pigeons (Columba livia) is impacted by both their geographical foraging area, and metal exposure in an urban context. First, pigeons were captured in 4 specific areas of Paris (France) and placed in captivity. By applying a 16SrRNA metabarcoding approach, we observed that the gut microbiota diversity was structured according to the capture sites, with strong variation of Actinobacteria, Bacilli and Clostridia, that could be linked to the granivorous or low-protein diets. Subsequently, we experimentally exposed these pigeons to zinc and/or lead (two-factor cross design) during 90 days in a non-urban environment, but no impact on the composition nor diversity of pigeon gut microbiota, has been observed after 45 and 90 days of metal exposures. However, the composition and diversity significantly differed from the microbiota at the capture period, with the emergence of taxa belonging to Corynebacterium and Bifidobacterium in captive conditions. These data highlight a strong impact of the lifestyles (captivity in non-urban environment) on the gut microbiota composition. In parallel, we hypothesized that the diet and the local environment might have smoothed the impact of the metal exposure for pigeons that could quickly change the structure of their gut microbiota. Our findings shed light on the effects of urban pollution and environment on bird communities, that can be extended to their gut microbiota causing potential additive or synergic negative effects to host organisms and populations.